REKAM JEJAK DAN POTENSI PENELITIAN DI BADAN USAHA MILIK DESA: STUDI BIBLIOMETRIK PUBLIKASI TAHUN 2015-2020 - Andre Kusuma; Hendrawan Santosa Putra; Sudarno Sudarno (Universitas Jember, 2021)
ABSTRACTThe development of BUMDes in Indonesia occurred after the issuance of Law No. 4 of 2015. This development is not only judged by the units formed but the number of studies as well. The development of BUMDes research has occurred significantly, this brings new needs so that these developments can be communicated. Bibliometrics are used to communicate the development of a discipline for further research needs. This study aims to map the development of research related to BUMDes from 2015-2020. The summary of this research is expected to be the starting point for further research in BUMDes studies. The research method used is quasi qualitative with bibliometric analysis. The research data is in the form of articles collected from the crossref meta data from 2015-2020. Filtering articles using the keywords